Creating Housing Markets in Emerging Market Economies - Innes, Cleo Rose (World Bank, Washington, DC, 2021)
At the beginning of the 20th century less than 15 percent of people across the globe lived in cities. This figure has risen to 50 percent (4.4 billion people) today and will exceed 66 percent (7.7 billion) by 2050. There is a significant shortfall of housing to meet the needs of people moving to cities, most of whom have limited resources but strong hopes for better educational and employment opportunities. Direct public provision of housing is not affordable for most national governments, so more than 1.6 billion people will struggle to secure housing by 2025. Addressing this under-provision of housing will require connecting capital with low-income urbanizing populations, including solutions to make the private sector more responsive to the investment opportunities that urbanization presents.